PROFIL BIOKIMIA DARAH PEKERJA LAKI-LAKI DENGAN KATEGORI RINGAN DAN BERAT - Yuniar Rosmalina; Fitrah Ernawati; Sukati Saidin (Persagi, 2009)
Biochemical Profile of Male Workers According To Hard or Light Works.Background: Various occupations could be categorized as light, moderate and heavy activities as well. Heavy workers by mean those who mainly work based on muscle strength usually received low salary, therefore they have low purchasing power for providing better nutrition, including for adequate energy intake. In contrary for those who work mainly using brain capacity rather than muscle strength usually received higher salary and consumed food with high content of fat. The difference of income could result difference of nutrition intake, even different impact to health/nutrition status and sensitivity to certain diseases as well. The profile of nutritional biochemistry could indicate the health status of people.Objectives: To study the relationship between biochemical profile of worker and different type of work.Methods: The subjects were 43 worker of sandal handicraft considered as light level workers and 44 workers of sand and stone as heavy workers whose met criteria 30-55 years old, physically healthy and agreed to involve in this study. Body composition was measured using anthropometry and blood analysis. Anthropometric measurement was applied including body weight, height, MUAC and skin fold thickness. Blood analysis was hemoglobin, albumin, protein and triglyceride. Nutrient intake was collected by combination weighing and 24 hours recall method for 3 consecutive days. Other data collection includes physical examination by a medical doctor and interview was done to identify their characteristic and socio demografi.Results: The proportion of workers who had serum albumin below normal was higher in heavy worker compared to light worker (56.8% vs. 23.3%). This finding indicated that more than half of hard workers had protein depletion as result of break down protein stores in thebody. The average of serum albumin of light workers was significantly higher compared to heavy workers. No significantly different based on the hemoglobin, protein and triglyceride concentration between the heavy and the light workers. The average energy and protein intake shows the heavy worker had higher intake on both nutrients compared to the lightworkers. The average energy intake of light worker was 1923 ± 295 Kcal and protein 41.6 ± 8.99 g, while the energy intake of heavy worker was 2232 ± 500 Kcal and protein 46.7 ± 14.7g.Conclusions: There was no significantly different found regarding biochemical profile oftwo workers, except serum albumin concentration. The lower profile of serum albumin concentration indicated that the heavy workers sacrificed of prolonged protein depletion of the body.Keywords: hemoglobin, protein, albumin, triglyceride, male worker.